Transaction Costs, Market Failure and Economic Development - Tamara Todorova (Journal of Advanced Research in Law and Economics, 2016)
This paper relates economic development to transaction costs. It reveals the triad transaction costs-market failure-economic underdevelopment. Many scholars attribute the problems of development to the failure of markets to perform their role of resource allocation. Some deny market failure and blame government instead. Of those who trace the roots of economic backwardness to market failure, few, if none, investigate transaction costs in their linkage with market failure. This paper tries to bridge development economics with transaction cost theory and new institutional analysis.
Keywords: D02; D23; O10; P14; 330; Transaction costs; Market failure; Opportunism; Economic development